Challenges experienced by postgraduate nursing students at a South African university - Yolanda Havenga; Malmsey L. Sengane (AOSIS, 2018)
Background: The increase in nurses enrolling in postgraduate programmes as well as the need to improve their completion requires academics to establish environments conducive for postgraduate studies. The challenges experienced during postgraduate studies have to be identified to establish conducive environments.   Objective: The objective of this study was to explore and describe the challenges experienced by postgraduate nursing students enrolled in postgraduate coursework and research programmes at a South African university.   Methods: An exploratory, descriptive and qualitative design was used. The study was contextual in nature. Purposive sampling was used. Fifteen honours, master's and doctoral students participated in the study. Data were analysed through qualitative content analysis and measures to ensure trustworthiness, and ethical implementation of the study were implemented.   Results: Three themes with categories were identified, namely personal challenges (i.e. finances, employment, family and accommodation), academic and institutional challenges (i.e. workload and time constraints, contact sessions, subject information and assessment) and research-related challenges (i.e. information literacy, supervisory relationship and supervisory structure and process). Conclusion: Institutional support addressing personal, academic and research-related challenges should be provided to enhance student experiences and completion.